2018
DOI: 10.1111/1365-2435.13088
|View full text |Cite
|
Sign up to set email alerts
|

Dryland soils in northern China sequester carbon during the early 2000s warming hiatus period

Abstract: Drylands, covering c. 45% of the Earth's terrestrial surface and supporting c. 38% of the global population, play a dominant role in the trend and interannual variability of global land carbon (C) sink. Given that a large proportion of organic C is stored in soils, our knowledge on soil C dynamics in drylands is crucial to evaluate terrestrial C‐climate feedback. However, credible understanding on this issue is still greatly limited by the lack of direct observations. Here, based on a regional resampling of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 68 publications
0
8
0
1
Order By: Relevance
“…The ten marked institutions almost were located in drylands in America, China, and Australia. Many studies have shown that drylands have a strong carbon sequestration potential (Tagesson et al, 2016;Kou et al, 2018;Abdi et al, 2019). America, China, and Australia cover tremedous typical semi-arid and arid areas at the global scale (Yang et al, 2019), and attach great importance to the trend and variability of the land carbon balance (Ahlstrom et al, 2015).…”
Section: Marked Institutionsmentioning
confidence: 99%
“…The ten marked institutions almost were located in drylands in America, China, and Australia. Many studies have shown that drylands have a strong carbon sequestration potential (Tagesson et al, 2016;Kou et al, 2018;Abdi et al, 2019). America, China, and Australia cover tremedous typical semi-arid and arid areas at the global scale (Yang et al, 2019), and attach great importance to the trend and variability of the land carbon balance (Ahlstrom et al, 2015).…”
Section: Marked Institutionsmentioning
confidence: 99%
“…In this study, we aim to access the effect of soil depth on soil microbial C : N : P stoichiometry along the aridity gradient. We hypothesized that the microbial C : N and C : P ratios decrease and the microbial N : P ratio increases with temperature Li et al, 2015;Xu et al, 2013), and the microbial C : N and C : P ratios decrease and the microbial N : P ratio increases with decreasing aridity index (Wang et al, 2014;Li et al, 2017). In addition, the identification of soil depth for vertical study is different in some published literature (Li and Chen, 2004;Aponte et al, 2010;Tischer et al, 2014;Peng and Wang, 2016).…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, less exploration of soil microbial stoichiometry along an aridity gradient at the regional scale impedes our ability to disentangle the trend of the changes in microbial stoichiometry amid climate changes. Climate change, such as global warming, is increasing the degree of aridity in drylands owing to the decreased precipitation and increased evaporation (Wang et al, 2014;Li et al, 2017). Given this background, key ecosystem processes that are regulated by soil microbes, such as soil respiration and nutrient mineralization, may be dramatically impacted by the increased degree of aridity, especially in fragile areas of arid and semiarid ecosystems (Delgado-Baquerizo et al, 2013;Chen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stocks of C, N, and P vary with soil depth, but their driving processes could be also different for thinning. Thinning causes fresh dissolved organic carbon from the topsoil to leach into the deep subsoil in subtropical regions, enhancing the effect of the deep soil C decomposition [13,14]. N deposition [15], litter decomposition [16], and rock weathering [17] contribute to soil N. N input with leaching intensifies the imbalance of N distribution in different soil layers.…”
Section: Introductionmentioning
confidence: 99%